Efek Domino OSS-RBA: Ketika Satu Platform Menentukan Masa Depan Ribuan UMKM - Sarjito, Aris (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study aims to evaluate the impact of the Online Single Submission – Risk-Based Approach (OSS-RBA) policy on the formalization and legal licensing of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Employing a qualitative-descriptive method and relying entirely on secondary data, the study focuses on assessing the effectiveness, efficiency, and responsiveness of OSS-RBA using a policy evaluation framework. The findings reveal systemic challenges in system integration, digital literacy gaps, and inconsistencies in local implementation. The study concludes that while OSS-RBA holds transformative potential, its execution poses barriers that may hinder MSME growth if not addressed. Recommendations include a phased digital transition, localized training, and improved system interoperability. Keywords: digital bureaucracy, formalization, OSS-RBA, policy evaluation, UMKM